Impact of Marriage on Career Development of Women: A Study of Newar Community of Kirtipur - Shakya, Sabina (Saptagandaki Journal, 2022)
The main objective of the research entitled Impact of Marriage on Career Development of Women: A Study of Newar Community of Kirtipur was to study the effects of marriage particularly on married women of the Newar community of Kirtipur and its impact on their career development. Both quantitative and qualitative approach were used as a mixed method. A cross sectional survey questionnaire was administered among the Newari married women of four wards - 3, 5, 9 and 10 ranging their ages from 24 to 45 to represent the total population of Kirtipur Municipality, Kathmandu. By purposive sampling method, 100 responses were collected and analyzed through SPSS V.20 for quantitative data and four cases were interviewed for qualitative data analysis. The data were analyzed on the basis of auto-ethnographic design. The study reveals the married women pursue less demanding jobs such as part-time and less effort making jobs due to household responsibilities. They cannot focus on career development to get opportunity in better workplace. The major contribution to the impact of marriage is engagement in household chores after marriage including taking care of their children until they are grown up for school.